Numerical investigation of the evolution of microstructure of nickel-based alloys during plastic working - Rogovoy, Anatoliy Alekseyevich; Salikhova, Nelli Kamilevna (Computational Continuum Mechanics, 2019)
The paper considers the process of hot plastic working of a large metal billet, which causes its upsetting to a dimension specified by the manufacturing technique and the average axial deformation of 32.5%. The billet was made of heat-resistant nickel alloy Waspalloy widely used in the aircraft industry. The structural condition of the deformed alloy and, consequently, its mechanical properties depend on many factors: the degree of deformation, the rate of deformation, recrystallization in the process of deformation. This generates a need for a comprehensive study of the plastic flow in the examined material and the influence of the deformation parameters on its characteristics. The paper presents the results of a numerical investigation of the deformation and temperature states of the billet that allowed us to analyze changes occurring in the structure of nickel alloy during plastic deformation at different upsetting rates (50 and 100 mm/s). The shape of billet lateral surface and the forces required to complete the process of free upsetting are calculated as well. The numerical simulation was performed by the finite element method using the DEFORM-2D/3D software package. The average grain size and the fraction of recrystallized grains in the body of the billet were determined based on the Johnson-Mehl-Avrami-Kolmogorov model (JMAK). The results of numerical modeling showed that the greatest change in the microstructure of the alloy occurs in the region of intense plastic strains. The upsetting rate of 100 mm/s leads to the formation of structure with finer grains compared to the structure formed at the upsetting rate of 50 mm/s.